Attrition and Retention of Sales People: A Diagnostic Study of the Insurance Sector - Sehgal, Mili; Pathak, Nitin (Prabandhan: Indian Journal of Management, 2015)
The insurance sector today stands as a business growing at a rate of 15-20% annually. In spite of spite of this growth, in the present scenario, the insurance industry is facing a grave challenge as far as retaining sales professionals is concerned. Around 35% attrition rate has been reported in the frontline sales category only. The present study aims to find out the factors that cause attrition in the insurance sector and how do these dimensions vary across the personal characteristics of the sales professionals.